Víctor Andrés Belaunde and Christian social thought - Gonzales Alvarado, Osmar (2018)
This article analyzes the set of reflections on Víctor Andrés Belaunde ‘s politics, characterized by the integral meaning he gave to his work. Thus, he addressed national problems from different disciplines: constitutional law, history, sociology, philosophy, theology, social psychology, international law, even from the political culture. As a result, Belaunde elaborates one of the most original analyzes of Peruvian political thought that the author tries to summarize and interpret in these pages.